If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 21 + -1j = 87 + -2j Solving 21 + -1j = 87 + -2j Solving for variable 'j'. Move all terms containing j to the left, all other terms to the right. Add '2j' to each side of the equation. 21 + -1j + 2j = 87 + -2j + 2j Combine like terms: -1j + 2j = 1j 21 + 1j = 87 + -2j + 2j Combine like terms: -2j + 2j = 0 21 + 1j = 87 + 0 21 + 1j = 87 Add '-21' to each side of the equation. 21 + -21 + 1j = 87 + -21 Combine like terms: 21 + -21 = 0 0 + 1j = 87 + -21 1j = 87 + -21 Combine like terms: 87 + -21 = 66 1j = 66 Divide each side by '1'. j = 66 Simplifying j = 66
| 2x-8+x=4x-10 | | 3G+3(-4+5G)=1-G | | 5(g+40)-7=103 | | -3(4x-2)=-30 | | -50-25n+3n^2=0 | | -(5x+7)+1=-5x-5 | | 3(6x-5)+2(5x+7)=3(9x+2) | | M-3m+3=3 | | 21-6d=22-8d | | 14-6-(-15)-18+(-7)= | | C=37.12+0.25 | | 7y-13=-58+2y | | 7-x/4=11 | | 9z+8z= | | x-(1/12)=(5/12) | | 2y-6=y | | 4x^2+3x=74 | | -7(1-8x)=105 | | 4z-25=-13+2z | | -9=-6+c | | 3G-3(-4+5G)=1-G | | 0=175-25n | | 11=7+2(5p+2) | | 2m-3=-6n | | 1x(1x+1)=42 | | 5(2x+3)=17.5 | | 5(x-4)+4+r=4(z+3)+x | | 11-3[a-2]=27 | | 3.16x+1.1=2.24x-2.00 | | -9+4n=7(n-5)-3(n+2) | | A=2(pi)(r)+2(pi)(r)(h) | | 4(4+4)=6(x-2) |